Dual Function Antibody Conjugates for Multimodal Imaging and Photoimmunotherapy of Cancer Cells. (25th August 2021) - Saad, Mohammad A.; Xavierselvan, Marvin; Sharif, Hamza A.; Selfridge, Scott; Pawle, Robert; Varvares, Mark; Mallidi, Srivalleesha; Hasan, Tayyaba
ABSTRACT: Precision imaging, utilizing molecular targeted agents, is an important tool in cancer diagnostics and guiding therapies. While there are limitations associated with single mode imaging probes, multimodal molecular imaging probes enabling target visualization through complementary imaging technologies provides an attractive alternative. However, there are several challenges associated with designing molecular probes carrying contrast agents for complementary multimodal imaging. Here, we propose a dual function antibody conjugate (DFAC) comprising an FDA approved photosensitizer Benzoporphyrin derivative (BPD) and a naphthalocyanine‐based photoacoustic dye (SiNc(OH)) for multimodal infrared (IR) imaging. While fluorescence imaging, through BPD, provides sensitivity, complementing it with photoacoustic imaging, through SiNc(OH), provides a depth‐resolved spatial resolution much beyond the optical diffusion limits of fluorescence measurements. Through a series of in vitro experiments, we demonstrate the development and utilization of DFACs for multimodal imaging and photodynamic treatment of squamous cell carcinoma (A431) cell line. The proposed DFACs have potential use in precision imaging applications such as guiding tumor resection surgeries and photodynamic treatment of residual microscopic disease thereby minimizing local recurrence. The data demonstrated in this study merits further investigation for its preclinical and clinical translation. Abstract : While single mode imaging techniques are popular in molecular imaging, they usually provide limited information regarding the target tissue. While combining complementary imaging modalities for molecular imaging is an attractive alternative, it is challenging to develop targeted probes carrying multiple contrast agents. This study demonstrates the development and evaluation of a fluorophore/photosensitizing agent and a sonochrome conjugated tumor‐targeted antibody—Cetuximab, as a targeted multimodal imaging probe—dual function antibody conjugate (DFAC), for tumor imaging and therapy. The DFAC proposed in this study can find potential application in surgical guidance through volumetric tumor visualization and photodynamic therapy of residual tumor tissues.